Success converting into Achievement - Manish Dudhagara (@Man) (Vidhyayana - An International Multidisciplinary Peer-Reviewed E-Journal - ISSN 2454-8596, 2022)
According to a person`s attitude, background, personality everybody thinks different about what is success. For some people who have done beginning from zero, if they get 25 to 30 thousand rupees per month and possess own a house of themselves they believe that they are successful in their lives. Where as a person doesn`t satisfy in these things just, he or she doesn`t believe that he or she has got success.